PENGARUH PEMBERIAN JUS LIDAH BUAYA (Aloe vera) dan JUS BELIMBING (Averrhoa carambola L.) TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI - Rai Riska Resti Wasista (Coping: Community of Publishing in Nursing, 2015)
The reduce of arteri and aorta elasticity cause the problem of bloodstream from heart is the beggining basic cause of the hypertens. Nonpharmalogical is an alternaitive treatment for hypertens, one of the most efective treatment is the combination of aloe vera juice and star fruit juice. Aloe vera and star fruit contain a nutrition called kallium and flavonoid. Kallium is very useful nutrition to hamper the renin in the angiotensin system where angiostensinogen couldn’t becoming angiostensin I form. Meanwhile flavonoid can accelerate the bloodstream and avoid the hamper of blood vassel. Aloe vera contain arginin that can make arterial wall becoming more elastic. This observation aims to evaluate the effect of aloe vera juice and star fruit juice in order to reduce the blood preasure of hypertens  eldery in the Elderly Social Institution Wana Seraya Denpasar.This observation is pre experiment study with one group pre-post test design. The sampling technique used total sampling with 19 subject of observation by meansure the blood preasure before and after the intervation for two weeks continously. The result of this observation show that 68,4% subject  has a significant decreased of systolic blood preasure and becoming normal, and 31,6% subject showing the indication of hypertens degree 1(140-159 mmHg). In other side the result also describing the decreased of dyastolic blood preasure, there are 52,6% subject has a normal dyastolic blood preasure (? 80 mmHg), 42,1% subject has a pre hypertens dyastolic blood preasure (80-89 mmHg) and just 5,3% subject who has hypertens degree 1 blood preasure (90-99 mmHg). Based on Wilcoxon statistic the p value in the systolic blood preasure is 0,000 and in the dyastolic blood presure is 0,005 thats mean there is significant effect of aloe vera and star fruit juice to reduce the blood presure of hypertens eldery in the Elderly Social Institution Wana Seraya Denpasar.